The Reality of Services Provided to Individuals with Autism Spectrum Disorder in Rehabilitation Centers in Western Region from Their Families’ Point of View - Almalki, Walaa Awadh; Ghareeb, Reem Mahmud (Journal of Educational and Psychological Sciences, 2022)
The study examined the reality of services provided to individuals with autism spectrum disorder (ASD) in rehabilitation centers in the western region, from the point of view of their families. A descriptive approach has been used to achieve the study objectives, with a sample including (165) families, and a questionnaire used as a key tool in collecting information.The study results showed that the services provided to individuals with ASD in rehabilitation centers were at a high standard, but the challenges dimension facing individuals with ASD in rehabilitation centers, were at an average level, and it is clear that the dimension of solutions that contribute to the development of services for individuals with ASD in rehabilitation centers was at a medium level.The researchers recommend the participation of families in all matters relating to their sons/daughters with autism spectrum disorder, and provision of free training courses for families.
Keywords: Autism Spectrum Disorder; Services; Rehabilitation Centers